2010
DOI: 10.1158/0008-5472.can-09-3880
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Autocrine Motility Factor Induces Mesenchymal-to-Epithelial Transition and Suppression of Osteosarcoma Pulmonary Metastasis

Abstract: Phosphoglucose isomerase (PGI) is a multifunctional enzyme that functions in glucose metabolism as a glycolytic enzyme catalyzing an interconversion between glucose and fructose inside the cell, while it acts as cytokine outside the cell, with properties that include autocrine motility factor (AMF)-regulating tumor cell motility. Overexpression of AMF/PGI induces epithelial-to-mesenchymal transition with enhanced malignancy. Recent studies have revealed that silencing of AMF/PGI resulted in mesenchymal-to-epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…Indeed, decreased expression of hexokinase 2 and glucose-6-phosphate isomerase genes has been associated with reduced cell growth. [39][40][41] We observed that these genes are also downregulated by statin treatment, leading to reduced glucose metabolism and consequent reduced cell proliferation, consistent with anticancer effects reported with statin treatment.Finally, we detected that the acetaldehyde dehydrogenase genes, ALDH1A1 and ALDH1B1, were downregulated by statin treatment. These enzymes are important in the ethanol degradation process whereby alcohol dehydrogenase oxidizes ethanol in the liver into acetaldehyde, which is then oxidized by acetaldehyde dehydrogenases into nontoxic acetic acid.…”
supporting
confidence: 87%
“…Indeed, decreased expression of hexokinase 2 and glucose-6-phosphate isomerase genes has been associated with reduced cell growth. [39][40][41] We observed that these genes are also downregulated by statin treatment, leading to reduced glucose metabolism and consequent reduced cell proliferation, consistent with anticancer effects reported with statin treatment.Finally, we detected that the acetaldehyde dehydrogenase genes, ALDH1A1 and ALDH1B1, were downregulated by statin treatment. These enzymes are important in the ethanol degradation process whereby alcohol dehydrogenase oxidizes ethanol in the liver into acetaldehyde, which is then oxidized by acetaldehyde dehydrogenases into nontoxic acetic acid.…”
supporting
confidence: 87%
“…Conversely to EMT, suppression of autocrine motility factor in various cancer cell lines induces MET (Niinaka et al, 2010). Expression of GATA3 in a breast cancer cell also reverses EMT, that is, induces MET (Yan et al, 2010).…”
Section: Cancer Cells S Floor Et Almentioning
confidence: 99%
“…It was shown that AMF/PGI mediates epithelial and mesenchymal phenotype conversions in breast cancer and its overexpression induces epithelial tomesen chymal transition with enhanced malig nancy and that silencing of AMF/PGI resulted in mesenchymaltoepithelial transition of human lung fibrosarcoma cells and breast cancer cells with re duced malignancy [24,25]. It was also shown that overexpression of AMF/PGI significantly contributes to the aggressive phenotype of human cancer, but downregulation of its expression and subsequent abrogation of AMF/PGI secretion is resulted in mor phologic change with reduced growth, motility, and invasion [25,26]. PGI/AFM also regulates endoplas mic reticulum stress and cell death through control of endoplasmic reticulum calcium release as well as promotes cell survival by the pAKT survival path way [27].…”
Section: We Have Studied the Effect Of Hypoxia On The Expression Levementioning
confidence: 99%